Oxford handbook of respiratory medicine. - Chapman, Stephen, 1953- Stephen Chapman, Grace Robinson, John Stradling, Sophie West, and John Wrightson; Robinson, Grace; Stradling, John R.; West, Sophie; Wrightson, John (Karachi : Oxford University Press, 2014)
Respiratory ailments are the most common reason for emergency admission to hospital, the most common reason to visit the GP, and cost the NHS more than any other disease area. This pocket-sized handbook allows instant access to a wealth of information needed in the day-to-day practice of respiratory medicine.
This edition for Pakistan only.
Includes bibliographical references and index.
Keywords: Respiratory organs -- Diseases